Characteristics, Antecedents, and Consequences of Non-Nursing Tasks: A Scoping Review Protocol. - Magro, Gaia; Bassi, Erika; Chiappinotto, Stefania; Dussi, Gaia; Ambrosi, Elisa; Canzan, Federica; Clari, Marco; Conti, Alessio; Dal Molin, Alberto; Palese, Alvisa (Nursing Reports, 2025)
Background: Nurses report that they often must perform activities outside their area of expertise, referred to as "non-nursing tasks". The time spent on simple tasks undermines nursing capacity, which is already challenged by the dramatic shortage of nurses. Performing non-nursing tasks affects nurses' satisfaction and their intention to stay. However, despite their relevance, there is no summary of studies on non-nursing tasks. The aim of this study is to summarize available evidence on characteristics of non-nursing tasks, their antecedents, and consequences, to identify gaps in the existing literature and to make recommendations for management, education, practice, and nursing research. Methods: A scoping review will be conducted using Arksey and O'Malley's methodological framework. The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews, and the Patterns, Advances, Gaps, Evidence for practice and research framework will be used to report and summarize the findings. Results: Findings will provide a map regarding the main patterns of research in this area and the evidence produced to date. Two main lines of findings are expected, namely the conceptual and the empirical. The former may contribute to the understanding of the terminology and concept used so far to clearly express non-nursing tasks; the empirical evidence may shed light on frequencies, instruments, reasons, and effects. Discussion: An analysis of non-nursing tasks will provide healthcare organizations with a conceptual framework of all variations in the phenomenon and will help managers to identify the activities that will fall within this conceptual construct. The establishment of a research strand in this field, based on a science-based review involving international stakeholders, can strengthen global action to prevent the occurrence of non-nursing tasks.